Analisis Keputusan Pemberian Kredit Pemilikan Rumah (KPR) Bagi Nasabah Pada Bank Tabungan Negara (BTN) Kc Karawang - Yuniar Maulidya; Sungkono Sungkono (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This article was created to find out how the decision to grant a Home Ownership Credit or KPR at BTN bank is. Lending has a very large risk that may be borne by the bank against the uncertainty of loan repayments from the debtor. The emergence of non-performing loans can then become a difficulty for the bank. Bank BTN plays an important role in providing mortgage loans to customers, in granting mortgage loans the bank must conduct research and proper calculations for prospective borrowers and many factors must be considered when making decisions in granting mortgages to customers, so that there are no mistakes in making decisions that are wrong. can result in losses to the bank, namely the possibility of bad credit. Seeing the frequent occurrence of bad credit risks borne by Bank BTN due to the uncertainty of debtor loan repayments, and where nonperforming loans can certainly affect the health of a bank. This study uses a qualitative method with a descriptive approach. This research study focuses on how the BTN bank, especially the KC Karawang, determines the decision to provide mortgage financing to its customers. The results of the study show that there are many series of processes until the decision to grant or the realization of the mortgage occurs. One of them is by checking BI, which is in the form of checking customer credit history, such as motorbike loans, car loans, credit on credit or paylater and others that will be seen in BI. If the BI is good and smooth, there are no arrears, then the mortgage application is accepted, but conversely, if the BI is not good, then the mortgage application will not be accepted.